Structural studies on cell walls of Pinus radiata : with particular reference to callus cultured cells : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry at Massey University, New Zealand - Fenemor, Dallas R. (Massey University, 1982)
A study of the composition of the primary cell wall of Pinus radiata has been undertaken. 1. Preliminary work with hypocotyl tissue showed that hemicelluloses of hypocotyl consisted of a xylan (probably (4-O-methylglucurono)xylan) and a xyloglucan. Acidic sugars examined, showed that galacturonic acid was the main component, and that 4-O-MeGlcA was present. 2. Cell walls were prepared from callus tissue either by wet sieving in 80% ethanol (Batch 1) or by disruption in a French Pressure cell and washing with aqueous potassium phosphate buffer; (Batch 2). Each batch was submitted to a series of extractions with different reagents in order to investigate the mode of bonding of polymers within the walls. The polysaccharide and protein components of each fraction were studied by monosaccharide and amino acid analysis. Fractions of Batch 1 were assayed for lignin and selected fractions from both batches were studied by methylation analysis. 3. The results of investigations led to the following major conclusions. The non-cellulosic components recognised in the wall preparations were: - a) A(1→3)-linked galactan and an arabino-3, 6-galactan which were largely extractable from the cell walls by hot water and may be only loosely bound in the cell wall. b) The pectic components consisting of; i) pectin, a galacturonate polymer containing a linear (1→4)-galacturonan back bone interspersed with branched rhamnose residues, ii) branched (1→5)-arabinan and iii) linear (1→4)-galactan, which occurred together in cell wall fractions and were not all extracted by classical extractants (such as hot aqueous EDTA), some being tightly bound in the cellulosic residue after alkali extraction. c) A fucogalactoxyloglucan some of which was extracted by water or EDTA, but the majority was extracted by subsequent treatment with either alkali or in part by a strong chaotropic reagent (6M GTC). Thus the fucogalactoxyloglucan was probably bound in the cell wall by strong hydrogen bonding. Some other bonding may be involved in the GTC-resistant fraction. d) A branched xylan which was removed by GTC and alkali, the larger level being removed by GTC. e) A galactoglucomannan, identified only by 4-linked mannose residues in hot water extracts and strong alkali fractions. f) Hydroxyproline-containing protein which was extracted from the cell wall by a variety of reagents but hydroxyproline-rich protein remains tighly bound after alkali extraction. g) Lignin which was tentatively identified in the cell wall. It appeared likely that cross-linking with lignin would be responsible for the non-extractability of some polysaccharides and protein from the walls. A mild acid chlorite treatment followed by alkali extraction removed most of the residual pectic components, xylan and protein from the walls. A basis has been laid for the further investigation of the wall structure and isolation of polysaccharides.
Keywords: Pinus radiata; Plant cell walls